Radial Junction Architecture: A New Approach to Stable and Highly Efficient Silicon Thin Film Solar Cells. Issue 1770 (2015) - Misra, S.; Foldyna, M.; Florea, I.; Yu, L.; Roca i Cabarrocas, P.
ABSTRACT: Incorporation of properly designed nanostructures in solar cells improves light trapping and consequently their power conversion efficiencies. Due to its unique structure, a silicon nanowire (SiNW) matrix provides excellent light trapping and thus offers a promising approach for cost-effective, stable and efficient silicon thin film photovoltaics. Moreover, by decoupling the light absorption and carrier collection directions, radial junction solar cells built around the SiNWs allow the use of very thin active layers. As a matter of fact, radial PIN junctions with 9.2% power conversion efficiency have already been demonstrated on glass substrates with only 100 nm thick intrinsic hydrogenated amorphous silicon layers. The most straightforward way to further improve the short circuit current density is to use an active layer with a lower band gap. In this work, the performances of devices with two different low band gap materials, e.g., hydrogenated microcrystalline silicon (μc-Si:H) and hydrogenated amorphous silicon germanium alloy (a-SiGe:H) are presented. To the best of our knowledge, this is the first demonstration of a-SiGe:H radial junction solar cell.